2021
DOI: 10.1001/jamanetworkopen.2021.5077
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preeclampsia With Incident Stroke in Later Life Among Women in the Framingham Heart Study

Abstract: IMPORTANCE Contemporary research suggests an association between preeclampsia and later-life stroke among women. To our knowledge, no research to date has accounted for the time-varying nature of shared risk factors for preeclampsia and later-life stroke incidence. OBJECTIVE To assess the relative risk of incident stroke in later life among women with and without a history of preeclampsia after accounting for time-varying covariates. DESIGN, SETTING, AND PARTICIPANTSThis population-based cohort study was a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…This is a critical time in the natural history of HDP as blood pressure is often higher and eclampsia is more likely to occur postpartum [ 25 , 26 ] reinforcing the need for targeted communication and postpartum monitoring. Responders also requested information regarding their long-term health, specifically cardiovascular disease, for which women with preeclampsia are at risk of [ 27 32 ]. Several also indicated poor counseling regarding the recurrence of HDP [ 33 , 34 ] and some were incorrectly informed that HDP would not recur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a critical time in the natural history of HDP as blood pressure is often higher and eclampsia is more likely to occur postpartum [ 25 , 26 ] reinforcing the need for targeted communication and postpartum monitoring. Responders also requested information regarding their long-term health, specifically cardiovascular disease, for which women with preeclampsia are at risk of [ 27 32 ]. Several also indicated poor counseling regarding the recurrence of HDP [ 33 , 34 ] and some were incorrectly informed that HDP would not recur.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, HDPs represent a unique pregnancy complication as they can present heterogeneously, progress rapidly, and have immediate high acuity impact on both mother and fetus, requiring complex medical decision-making. HDPs also have long-term impact on maternal and offspring health [ 30 32 , 35 ], adding complexity to communications. As most pregnancies proceed without incident, diagnosing HDP can be challenging, especially in nulliparas.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the literature, previous studies reported the stroke risk for 3 months antepartum, and 3 days, 6 weeks, 6 months, and 12 months postpartum [ 14 ]. For follow up time exceeded one year after delivery, only one longitudinal cohort study recently had ever reported the later-life stroke incidence [ 24 ], but their study did not compare stroke risk in different time intervals. Because no specific time division criteria could be referred, we conventionally divided the follow-up time into 0–5, 5–10, and 10–15 years, and further divided the 0–5 years close to delivery into 0–1, 1–3, and 3–5 years.…”
Section: Methodsmentioning
confidence: 99%
“…Cerebrovascular disorders are the leading cause of maternal mortality in PE, predominantly as a consequence of intracerebral hemorrhage or stroke (Bushnell et al, 2014; Duley, 2009; Fishel Bartal & Sibai, 2020; Miller, 2019). According to a recent cohort study based on the data of Framingham Heart Study, women with PE have a more than threefold higher risk for future stroke (de Havenon et al, 2021). Cerebrovascular disorders of PE include increased blood‐brain barrier (BBB) permeability, subsequent brain edema, visual disturbances, seizures (eclampsia), neurovascular dysfunction, perivascular microhemorrhage, microinfarcts, arteriolar vasculopathy, and stroke (Hammer & Cipolla, 2015; Kontos et al, 1978; Kontos et al, 1981; Logue et al, 2016; Mahendra et al, 2021; Miller, 2019; Paulson, 2002; Ryan et al, 2011; Warrington et al, 2014; Younes & Ryan, 2019; Zunker et al, 2000).…”
Section: Pathomechanisms Of Preeclampsiamentioning
confidence: 99%